The Influence of the VCT (Value Clarification Technique) Learning Model Based on Local Wisdom on the Character Values of Elementary School Students - Fira Astika Wanhar; Nurlia Ginting; Fatmawati Fatmawati; Yusrizal Yusrizal (Journal of General Education and Humanities, 2026)
This study investigates the effect of a local wisdom-based Value Clarification Technique (VCT) model on elementary students’ personality character values in geometry learning. The research addresses the limited integration of character education within cognitively oriented mathematics instruction. The objective is to examine differences in personality character values between students taught using the VCT model integrated with the ulos sadum cultural motif and those receiving conventional instruction. A quantitative true experimental design with a posttest-only control group was employed. A total of 120 fourth-grade students were randomly assigned to experimental and control groups. Data were collected using a validated questionnaire measuring moral knowing, moral feeling, and moral action. Instrument validity and reliability were confirmed through confirmatory factor Analysis using PLS-SEM. Statistical analyses included normality and homogeneity tests, Pearson correlation, and simple linear regression. The results indicate a significant difference between groups, with the experimental group achieving higher character scores. The VCT model accounted for 54.5% of the variance in personality character values. The findings demonstrate that integrating value clarification with culturally contextualised mathematics learning effectively strengthens students’ character development.